Práticas contábeis na gestão das empresas brasileiras operadoras de cruzeiros marítimos: um estudo de caso - Contini, Márcio Cláudio (2010)
The activity of tourism maritime cruise operation started in Brazil over 60 years ago, although it has gained space in the national economic scenario just recently, thus emerging as one of the country's main and most promising tourism modalities. Encouraged by the excellent cruise seasons of the decade, foreign ship companies, local businessmen, governmental entities and the society in general, turn their attention to this segment. In the 2008/2009 season, for example, ship companies served about 520 thousand guests in their 16 ships. If this volume were not enough high, the segment announces 18 ships for the 2009/2010 season, with capacity to attend 920 thousand guests. Estimates in the sector on the potential of this activity point out that the market may reach the mark of 2 million passengers in short time. For all this volume of guests served and the segment potential scope, the operation of maritime cruises in the country is still little known, mainly as to the accounting and management approach. Many are the actors involved in this process who take part in the several steps of this activity's production chain. The cruise operating company relates to each one of them and carries out basic functions of promoting and selling cruises, as well as that of administering a few activities while the ships are in national waters. For this purpose, they interact with the very foreign ship company, travel agencies, representative agencies, port agencies, government entities, several suppliers and, of course, passengers. The organization and management of all these relationships is something that can be very complex on the operational point of view. In this sense, the importance of the accounting control of these companies has been confirmed. The operating company's controllership division has been outstanding as it develops and exceptional work of managing these relationships. Based on a solid accounting foundation, these divisions have been meeting the needs of managers, thus producing information of a relevant nature and in proper time, helping the business management process. It is in the accounting sphere that these companies search for a relevant part of the operation information and which encompasses a few interesting specificities under the accounting perspective. The management of charter contracts, advance payments received by passengers, advance payment of commissions to travel agents or marketing expenses, the entry of revenues resulting from the sale of coastal or international cruises, among others, are aspects that are considered part of this set of specificities. Likewise, the relationships with the ship companies are also specific topics of this segment. We can note that the management of the cash flow and these coastal cruise contracts are key factors for the success of these businesses. This case study, developed with two of the main cruise companies of the Brazilian cruise industry, Ibero Cruzeiros and Costa Cruzeiros, does an analysis in detail of the aspects of this activity, contributing for the knowledge formation of the tourism cruise operation and the importance of the accounting control in these companies as well as the accounting practices used by the operators in the control of the main operations